The Maiden of the Buhong Sky. [anthology].
The Maiden of the Buhong Sky" is one of the many songs about the Manuvu hero, "Tuwaang". In 1,417 lines, the song narrates how Tuwaang comes to the assistance of a mysterious maiden from the skyworld and how in the end he takes her and his people to the country of Katuusan, the "land without death".
Found in: Philippine Folk Literature: The Epics. (GR 325 P48 2001 v.8)
Keywords: Literature-Collections.